IUS Constituendum of Suistainable Agricultural Policy: The Aftermath of Job Creation Act - Fahamsyah, Ermanto; Chansrakaeo, Ruetaitip (Jurnal IUS Kajian Hukum dan Keadilan, 2022)
Agriculture is an important aspect of the life of the Indonesian people. Apart from being a commodity, agriculture is also a part of Indonesian social lives. In this case, the state needs to enact legal policies related to sustainable agriculture. This study seeks to discuss legal issues in the form of legal disharmony related to sustainable agricultural legal policies. The study results confirm that the disharmony of legal policies related to Sustainable Agriculture has only become “ineffective,” which means that the rules exist but cannot be implemented because they do not have the implementing regulations. This happens because the respective laws, particularly those related to sustainable agricultural cultivation systems and job creation, which substantially regulate sustainable agriculture, do not refer to each other. That affects the lack of coordination and horizontal harmonization between laws that substantially regulate sustainable agriculture. Harmonization was not carried out vertically, between laws and government regulations. This occurs when government regulations related to the administration of the agricultural sector do not refer to, and vertically disharmony with the Law relating to sustainable agricultural cultivation systems. The results of this study suggest that in the future, in this case, the government requires to revise the Government Regulations on the implementation of the agricultural sector by incorporating the substance of the sustainable agriculture policy as well as being more thorough in harmonizing both vertically and horizontally in drafting legislation.